2022
DOI: 10.1158/2767-9764.crc-22-0056
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Engineered Toxin Body MT-3724 in Relapsed or Refractory B-cell Non-Hodgkin's Lymphomas and Diffuse Large B-cell Lymphoma

Abstract: PURPOSE: MT-3724, a novel engineered toxin body comprised of an anti-CD20 single-chain variable fragment genetically fused to Shiga-like Toxin A subunit, is capable of binding to and internalizing against CD20, inducing cell killing via permanent ribosomal inactivation. This study evaluated MT-3724 in patients with relapsed/refractory B-cell Non-Hodgkin lymphoma (r/rNHL). METHODS: This open-label, multiple-dose Phase 1a/b trial included a dose escalation in patients with r/rNHL according to a standard 3+3 desi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The median DOR, PFS, and OS were 13.4, 5.6, and 20.1 months, respectively [28]. In R/R DLBCL patients of auto-SCT ineligible, although the Pola-BR group had higher rates of grade 3-4 neutropenia, anemia, and thrombocytopenia (but similar rates of grade Other ADCs, such as anti-CD19 [35], anti-CD20 [36], anti-CD22 [28], anti-CD25, anti-CD37, and anti-CD70, had been investigated previously. Among these, MT-3724, capable of binding to and internalizing against CD20, is a novel engineered toxin body [36].…”
Section: Polamentioning
confidence: 98%
See 2 more Smart Citations
“…The median DOR, PFS, and OS were 13.4, 5.6, and 20.1 months, respectively [28]. In R/R DLBCL patients of auto-SCT ineligible, although the Pola-BR group had higher rates of grade 3-4 neutropenia, anemia, and thrombocytopenia (but similar rates of grade Other ADCs, such as anti-CD19 [35], anti-CD20 [36], anti-CD22 [28], anti-CD25, anti-CD37, and anti-CD70, had been investigated previously. Among these, MT-3724, capable of binding to and internalizing against CD20, is a novel engineered toxin body [36].…”
Section: Polamentioning
confidence: 98%
“…Other ADCs, such as anti-CD19 [ 35 ], anti-CD20 [ 36 ], anti-CD22 [ 28 ], anti‑CD25, anti‑CD37, and anti‑CD70, had been investigated previously. Among these, MT-3724, capable of binding to and internalizing against CD20, is a novel engineered toxin body [ 36 ]. In a phase Ia/b trial, MT-3724 showed an ORR of 41.7% in R/R DLBCLs with serum rituximab negative [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the relatively poor internalization of CD20, few ADCs and immunotoxins were developed. A single-chain variable fragment-based targeting CD20 and conjugated with Shiga-like toxin A subunit, MT-3724, presented promising preclinical and early clinical results, but its development was ceased by the manufacturer ( 38 ). Another strategy that does not require CD20 internalization for direct and targeted cell killing is the use of radio-immunoconjugates.…”
Section: Anti-cd20 Mabs and Immunoconjugatesmentioning
confidence: 99%
“…The majority of mAbs are characterized as type I, which exhibit the ability to cluster CD20 into membrane lipid rafts, which is associated with potent induction of CDC. On the other hand, type I antibodies display a higher rate of internalization, which can limit their therapeutic efficacy (36). Type II mAbs do not stabilize CD20 in lipid rafts and are weak inducers of CDC, but they potently evoke direct cell death (37).…”
Section: Anti-cd20 Mabs and Immunoconjugatesmentioning
confidence: 99%